TINJAUAN SOSIO YURIDIS PERKELAHIAN ANTARA PEMUDA DI KELURAHAN BONE-BONE DAN KELURAHAN TARAFU KOTA BAUBAU SULAWESI TENGGARA - La Ode Ali Mustafa; Galing Sawung Galing Ade (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This study aims to determine the factors that led to fights between youths in the Bone-Bone Sub-District and Tarafu Sub-District and the efforts of the police to prevent fights between youths from occurring. This research was conducted in Baubau City, Batupoaro District, Bone-Bone Village with the research location in Bone-Bone Village. Data collection techniques through direct interviews with related parties from the results found the fact that the factors that occur in fights between youths are education, family environment, age factor, revenge factor, alcohol, and lack of space for self-development in adolescents. As for the efforts of the police apparatus, there are 3 efforts to deal with pre- emptive, preventive, and repressive efforts while the efforts of the Bone-Bone sub-district government are to provide understanding and also provide business assistance to youth.